2016
DOI: 10.1007/s40653-016-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Sleep as a Mediating Variable Between Exposure to Interparental Violence and Depression Severity in Adolescents

Abstract: Exposure to violence, including interparental and peer dating violence, is a public health concern associated with negative outcomes, including depression. However, little is known about mechanisms by which exposure to violence influences depressive symptoms. One factor that may help explain this association is problematic sleep. This study sought to determine whether short sleep duration mediates the relationship between exposure to violence (interparental and peer dating violence) and depressive symptoms. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…This finding is consistent with the one existing study investigating links between conflict property appraisals and objectively measured sleep, which found that appraisals of more frequent, intense and poorly resolved conflict were indirectly related to sleep quality and duration through children's emotional security (El-Sheikh et al, 2006). Other studies investigating the effects of IPC have found similar results, although they utilized measures of interparental violence or openly expressed anger in relation to self-reported sleep (Nowakowski et al, 2016;Zhang et al, 2018). Therefore, this study adds to the literature about the ways that IPC disrupts adolescent sleep, highlighting perceptions of conflict as frequent, hostile or poorly resolved as particularly important for predicting sleep patterns.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with the one existing study investigating links between conflict property appraisals and objectively measured sleep, which found that appraisals of more frequent, intense and poorly resolved conflict were indirectly related to sleep quality and duration through children's emotional security (El-Sheikh et al, 2006). Other studies investigating the effects of IPC have found similar results, although they utilized measures of interparental violence or openly expressed anger in relation to self-reported sleep (Nowakowski et al, 2016;Zhang et al, 2018). Therefore, this study adds to the literature about the ways that IPC disrupts adolescent sleep, highlighting perceptions of conflict as frequent, hostile or poorly resolved as particularly important for predicting sleep patterns.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond general stress, which is a robust predictor of problematic health and related outcomes (Cohen, Kamarck, & Mermelstein, 1983), exposure to hostile, frequent and/or poorly resolved IPC is a robust stressor, and therefore an important predictor of adjustment for children and adolescents, both cross‐sectionally and over time (Fosco & Feinberg, 2015; Rhoades, 2008; Zimet & Jacob, 2001), as well as between and within person (Fosco & Lydon‐Staley, 2017). IPC exposure also predicts reductions in the quality and quantity of sleep for children and adolescents (El‐Sheikh, Buckhalt, Mize, & Acebo, 2006; Nowakowski, Choi, Meers, & Temple, 2016; Zhang, Yang, Liu, Jia, & Liu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to highlight that the present investigation is one of only a very few longitudinal studies conducted outside of North America, perhaps one of the first that focused on the links between sleep duration and both internalizing and externalizing problems, as well as academic competence; in addition, it also tested these links with sleep quality. Study findings mostly replicated previous findings on the longitudinal relationships between sleep and key adolescent adjustment measures in this sample of Czech youth (e.g., Nowakowski et al, 2016, in the United States; Bonnar et al, 2015, in Australia; Chan et al, 2018, in Hong Kong). Short et al (2020) highlighted how low sleep duration (quantity) is associated with a variety of mood deficits (e.g., depressed mood, anxiety, anger), increasing the likelihood of mood problems by 55% ( OR = 1.55, 95% CI [1.44, 1.67]).…”
Section: Discussionsupporting
confidence: 87%
“…In particular, sleep problems mediated the prospective effect of community violence exposure or victimization on lower academic achievement, delinquency, and substance use in early adolescents (Lepore & Kliewer, 2013; Sosnowski et al, 2016). Similarly, inadequate sleep mediated the effects of exposure to interparental violence on adolescents’ depressive symptoms (Nowakowski, Choi, Meers, & Temple, 2016). Indeed, poor sleep has been proposed as a key mediator explaining both psychological and health problems in youth exposed to traumatic events, such as violence (Spilsbury, 2009).…”
Section: Discussionmentioning
confidence: 99%